Sister City Surabaya - Liverpool: Tinjauan Yuridis Berdasarkan Perspektif Hukum Indonesia dan Vienna Convention on the Law of Treaties (VCLT) 1969 - Sagala, Kaleb Anggi Three Putra; Nababan, Roida; Simamora, Sovia; Sagala, Christo Sumurung Tua (INTERDISCIPLINARY JOURNAL ON LAW, SOCIAL SCIENCES AND HUMANITIES, 2024)
This research aims to examine more deeply the authority of local governments in conducting parallel diplomacy. By using a descriptive qualitative approach. The purpose of this research is to find out that Liverpool and Surabaya's cooperation in the creative industry has resulted in useful projects. Educational cooperation, urban cooperation, and port management development are some of the activities that have been implemented in the sister city agreement. The results showed that the application of pacta sunt servanda in the MOU is going well, because it has experienced many significant developments such as developments in the MSME business and the opportunity to introduce Surabaya products to the city of Liverpool. Able to encourage other local governments to carry out international agreements to build and develop a region. This cooperation is very important as an alternative to increasing income and supporting technological backwardness in the region.Keywords: Sister City, Cooperation, Pacta Sunt Servanda, International Agreement.